2016
DOI: 10.1542/hpeds.2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Family Experience With Hospitalization for Neonatal Abstinence Syndrome

Abstract: A B S T R A C T BACKGROUND AND OBJECTIVES:Although the incidence of neonatal abstinence syndrome (NAS) in the United States quintupled between 2000 and 2012, little is known about the family perspective of the hospital stay. We interviewed families to understand their experiences during the newborn hospitalization for NAS and to improve family-centered care. CONCLUSIONS: Families face many challenges during newborn hospitalization for NAS. Addressing parental needs through improved perinatal education, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Similar to Atwood et al, 14 we found that any separation of the infant from the mother at any stage of the birth hospitalization, competing medical demands by the mother, and logistical transportation issues impacted mothers' ability to remain at the bedside. These data can be used to emphasize the importance of hospital policies to minimize mother-infant separation during the birth hospitalization and of assistance with transportation as key aspects of future interventions to maximize rooming-in.…”
Section: Feelings Of Internal and External Stigma Negatively Impact Msupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to Atwood et al, 14 we found that any separation of the infant from the mother at any stage of the birth hospitalization, competing medical demands by the mother, and logistical transportation issues impacted mothers' ability to remain at the bedside. These data can be used to emphasize the importance of hospital policies to minimize mother-infant separation during the birth hospitalization and of assistance with transportation as key aspects of future interventions to maximize rooming-in.…”
Section: Feelings Of Internal and External Stigma Negatively Impact Msupporting
confidence: 82%
“…In a single qualitative study of families of infants with NAS, the authors reported that the physical environment, transportation issues, and mothers' medical needs impacted roomingin. 14 This study was performed at a large academic center in a rural area at a time when infants with NAS who received pharmacologic treatment were removed from their mothers' rooms and cared for in an open-layout NICU. 14 Mothers' experiences with rooming-in within different models of NAS care (in which infants do not routinely receive treatment in the NICU) or mothers living in urban settings have not been explored.…”
mentioning
confidence: 99%
“…18 In the second PDSA cycle, we conducted qualitative interviews with families of newborns hospitalized with NAS, which yielded information that shaped further PDSA cycles (Table 1). 19 Families informed us that some infants were being awakened from sleep for scoring, given points for crying when hungry, and removed from family members' arms to be assessed. PDSA cycle 3 changed the timing of NAS scoring to every 2 to 4 hours just after each feeding, during skin-to-skin holding, while the infant and family were already awake ("infant-centered scoring").…”
Section: Planning the Interventionmentioning
confidence: 99%
“…PDSA cycle 3 changed the timing of NAS scoring to every 2 to 4 hours just after each feeding, during skin-to-skin holding, while the infant and family were already awake ("infant-centered scoring"). Because families desired more education about NAS and direct involvement in care, 19 PDSA cycle 4 involved prenatal preparation sessions at 2 local perinatal substance abuse treatment centers and updated education materials on NAS for obstetric clinic appointments. In PDSA cycle 5, we incorporated parent symptom recording into care processes.…”
Section: Planning the Interventionmentioning
confidence: 99%
See 1 more Smart Citation